Effect of Green Polymerisation Via Microwave-Assisted Synthesis on Morphology, Size, and Rebinding Properties of Aspirinate Molecularly Imprinted Polymer - Vannessa, Lawai; Zainab, Ngaini; AHMAD ANIQ, NOOR BAHAR (UMT Press, 2025)
Molecularly imprinted polymer (MIP) has been vastly investigated for various applications, including drug delivery systems. Precipitation polymerisation has been widely used in the preparation of MIP to obtain small-sized polymer beads that are vital in drug delivery applications. However, the process requires a longer time and produces larger polymer particles, which often appear as a constraint for large-scale production and drug delivery applications. In this study, a series of MIPs were synthesised via microwave (MW) irradiation employing aspirin as a template in the presence of methacrylic acid (MAA) as functional monomer and divinylbenzene as crosslinker in acetonitrile at 80°C (MW80 in 60 minutes), 100°C (MW100 in 15 minutes), 110°C (MW110 in 8 minutes) and 120°C (MW120 in 4 minutes). MW110 produced homogeneous spherical particles (1.24 μm ± 0.17 μm), higher yield (0.62 g) and excellent rebinding capacity (7.27 mg/g) compared with other MIPs. Green synthesis of MIP via MW emerged as a powerful tool for well-controlled, rapid reactions and is significantly useful for drug delivery applications.